Influence of infant microbiome on health and development - Noelle Younge (The Korean Pediatric Society, 2024)
The microbiome is a complex ecosystem comprising microbes, their genomes, and the surrounding environment. The microbiome plays a critical role in early human development, including maturation of the host immune system and gastrointestinal tract. Multiple factors, including diet, anti-biotic use, and other environmental exposures, influence the establishment of the microbiome during infancy. Numerous studies have identified associations between the microbiome and neonatal diseases, including necrotizing enterocolitis, sepsis, and malnutrition. Furthermore, there is compelling evidence that perturbation of the microbiome in early life can have lasting developmental effects that increase an individual's risk for immune and metabolic diseases in later life. Supplementation of the microbiome with probiotics reduces the risk of necrotizing enterocolitis and sepsis in at-risk infants. This review focuses on the structure and function of the infant microbiome, the environmental and clinical factors that influence its assembly, and its impact on infant health and development.